Factors Related to Prevention of Dengue Hemorrhagic Fever in South Birobuli - Rau, Muh. Jusman; Soraya, Nadia; Pitriani, Pitriani (Tadulako University, 2019)
Dengue Hemorrhagic Fever is a health problem that is contagious in tropical regions like Indonesia. Central Sulawesi data in 2017 the highest DHF cases are Palu City with 401 cases and Incidance Rate of 103.95 / 100,000 population with CFR of 0.49% and IR which is still above the national indicator that is 52 / 100,000 population. In 2017 the incidence of DHF in the South Bureau of South Bureau was reported as many as 26 cases of DHF with 1 person dead. The development of this disease is very fast and causes death in a short time, one of the factors causing DHF cases is climate change. The purpose of this study was to determine the Factors Associated with Efforts to Prevent Dengue Fever in the South Birobuli Village. The population in this study was the head of the family of 1,999 households using the Lameshow formula, the number of samples was 92 households taken by each RW. The sampling technique was using proportional stratified random sampling and using the chi-square test. Data analysis was performed univariately and bivariately at 95% confidence level (α = 0.05). The results showed knowledge (p = 0.021), attitude (p = 0.003), facilities (p = 0,000) and the role of health workers (p = 0,000), related to dengue prevention efforts. It is hoped that the P2 program manager in Dipuskesmas can increase counseling on dengue prevention efforts by eradicating mosquito nests such as the implementation of 3M plus regularly and continuously so that the community is able to be independent and routinely conduct dengue fever prevention efforts.